1987
DOI: 10.1016/0014-5793(87)80138-2
|View full text |Cite
|
Sign up to set email alerts
|

cAMP reduces the affinity of Ca2+‐triggered secretion in platelets

Abstract: Prostacyclin and other related compounds known to increase intracellular cAMP levels inhibit platelet responses. The mechanisms involved are only partially known, especially those concerning the complex relations between Ca 2 ÷ and cAMP as opposite intracellular mediators. Here, we have investigated aggregation and secretion in quin2-1oaded platelets under conditions in which Ca 2 ÷ and cAMP are the only intracellular mediators. Our results show that cAMP inhibits aggregation and secretion in ionophore-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…The Ca2+-dependent phosphorylation of the 20 and 47 kDa proteins induced by ionophore A23187 was not inhibited by PGI2. In agreement with previous studies [10,33,34], aggregation but not shape change was inhibited by PGI2. Since Ca2+ mobilization induced by ionophore A23187 was not inhibited by PGI2 (see also refs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The Ca2+-dependent phosphorylation of the 20 and 47 kDa proteins induced by ionophore A23187 was not inhibited by PGI2. In agreement with previous studies [10,33,34], aggregation but not shape change was inhibited by PGI2. Since Ca2+ mobilization induced by ionophore A23187 was not inhibited by PGI2 (see also refs.…”
Section: Discussionsupporting
confidence: 93%
“…Since Ca2+ mobilization induced by ionophore A23187 was not inhibited by PGI2 (see also refs. [33,34]), these results indicate that aggregation is inhibited by PGI2 at steps distal to Ca2+-dependent phosphorylation of 20 and 47 kDa proteins. This result is somewhat unexpected: biochemical studies using purified proteins have demonstrated that protein kinase A phosphorylates MLCK, thereby diminishing its enzymic activity and decreasing its affinity for calmodulin [4,37].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…For this, cAMP activates a protein kinase that phosphorylates an ATP-dependent calcium-pump. Subsequently, Ca 2+ uptake into the dense tubular system is subsequently decreased, resulting in the inhibition of platelet activation cascades [83][84][85]. In the present study, we found that treatment with baicalein elevated the level of cAMP in resting platelets.…”
Section: Discussionmentioning
confidence: 65%
“…Other studies discovered additional target sites for platelet inhibition by cyclic AMP. For example, several investigators reported that cyclic AMP inhibits secretion and aggregation induced by Ca2+ ionophore at steps distal to Ca2l mobilization [6][7][8][9]. Also, modest increments in platelet cyclic AMP were reported to abolish platelet-activatingfactor-induced aggregation and secretion, whereas they had little effect on phosphoinositide hydrolysis and elevation of cytosolic Ca2+ concentration induced by platelet-activating factor [10].…”
Section: Introductionmentioning
confidence: 99%